Penggunaan Pot Berbahan Dasar Organik untuk PembibitanGmelina arborea Roxb. di Persemaian - Sri Wilarso Budi; Andi Sukendro; Lina Karlinasari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
The objectve of this research was to obtain the best materials composition and adhesive of organic pot for forest trees seedling production. Organic pot strength was evaluated by testing the strength of rupture elasticity and elasticity stiffness of each composition. The bioassay testing used Completely Randomized Design with factorial pattern, consisting of two factors, (1) basic raw materials of the pot (used newspaper, litter and compost) and (2) the type of adhesive (control, tanin and starch). The results showed that the adhesive starch gave higher strength, whereas adhesive tannin gave higher stiffness as compared to control. Results of bioassay showed that the mixture (50:50 v/v) of basic materials of used newspaper and compost (KKK) which were glued with tannin, produced the best results for height and diameter increament with the value of 35.85 cm, 0.31 cm respectively and biomass value of 0.99 g after 12 weeks of planting. The highest level of damage in organic pot with basic raw materials KKK without adhesive was 47.6%, whereas lowest level of damage in organic pot with basic raw material used newspaper (KK) with tannin addhesive was 2.0% after 12 weeks in the nursery.Keywords: adhesive, Gmelina arborea,organic pot, organic matter, nursery,